The Moro way of life in southwestern Mindanao and the Philippine public school system - San Agustin, Araceli (Sebastian) (1959)
The main purpose of the author was to describe some elements in Moro culture to show some discrepancies between this culture and the present educational system, and to suggest ways and means of eliminating such discrepancies in order to provide the Moros with a better and more functional type of education. The identification of significant inconsistencies between the present educational policy and the Moro culture seems to be the first step in the intelligent solution of integrating the Moro with Christian Filipinos.